Chaotification for Partial Difference Equations via Controllers. (13th March 2014) - Liang, Wei; Shi, Yuming; Li, Zongcheng
Abstract : Chaotification problems of partial difference equations are studied. Two chaotification schemes are established by utilizing the snap-back repeller theory of general discrete dynamical systems, and all the systems are proved to be chaotic in the sense of both Li-Yorke and Devaney. An example is provided to illustrate the theoretical results with computer simulations.